2016
DOI: 10.21276/sajb.2016.4.6.12
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profile of Bile in Patients Undergoing Cholecystectomy

Abstract: Cholecystitis and cholelithiasis are frequently met surgical conditions in North India. The presence of bacteria in bile at the time of surgery or invasive diagnostic procedures predisposes to complications like septicaemia. Aim of this study was to study the bacteriological profile -aerobic & anaerobic in the bile of patients undergoing cholecystectomy. The present study included 50 patients admitted in the department of general surgery undergoing cholecystectomy with preoperative diagnosis of biliary tract d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Gram positive bacteria -Enterococcus species and Candida species were predominantly seen among the 36 polymicrobial infections. These findings are similar to studies reported elsewhere 16 . Aeromonas hydrophila (n=2) was isolated from bile as monomicrobial pathogen.…”
Section: Discussionsupporting
confidence: 93%
“…Gram positive bacteria -Enterococcus species and Candida species were predominantly seen among the 36 polymicrobial infections. These findings are similar to studies reported elsewhere 16 . Aeromonas hydrophila (n=2) was isolated from bile as monomicrobial pathogen.…”
Section: Discussionsupporting
confidence: 93%
“…Our results were similar to studies published by Ballal et al in 2001, (7) Devangan et al in 2015. (8) Gill et al in 2016 (1) has reported a slightly higher incidence of bacterbilia of about 30-35%. In a study by Capoor et al (2008), (9) most common organism was isolated was E. coli followed by Klebsiella pneumonia, Citrobacterfreundii and Salmonella.…”
Section: Discussionmentioning
confidence: 95%
“…(1) Human bile is normally sterile. However in biliary tract obstruction bacteria may gain access to the biliary tract through papilla of vater or portal circulation.…”
Section: Introductionmentioning
confidence: 99%
“…(68.42%). [41] Out of 246 bile samples, S . Typhi was detected in 3 (1.22%) by culture and in 8 (3.25%) by PCR which reported similar in different studies [18,41] but higher prevalence (8-14%) were reported by some studies which might be due to hyperendemicity of the study area.…”
Section: Discussionmentioning
confidence: 99%
“…[41] Out of 246 bile samples, S . Typhi was detected in 3 (1.22%) by culture and in 8 (3.25%) by PCR which reported similar in different studies [18,41] but higher prevalence (8-14%) were reported by some studies which might be due to hyperendemicity of the study area. [8,13,41] Of gram-positive cocci, S. aureus was found in 24 (19.35%) cases in this study which correlates with the study by Suri et al[42] Lower isolation rate (2.1%) and higher isolation rate (29.67%) were reported in different studies which might be due to geographical variation and antibiotic policy of the respective country.…”
Section: Discussionmentioning
confidence: 99%